2021
DOI: 10.3390/life11070640
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Components of Nitrogen Fixation Gene Cluster and Associated Enzymatic Activities of Non-Heterocystous Thermophilic Cyanobacterium Thermoleptolyngbya sp.

Abstract: Thermoleptolyngbya is a genus of non-heterocystous cyanobacteria that are typical inhabitants of hot spring microbial mats. These filamentous cyanobacteria are capable of nitrogen fixation. In this study, we examined the genome sequences of five publicly available Thermoleptolyngbya strains to explore their nitrogen fixation gene cluster. Analysis of the nitrogen-fixation clusters in these extremophilic strains revealed that the cluster is located in a single locus in Thermoleptolyngbyace. The average nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Physiological assessment of the strain was performed using BG-11 medium free of an essential nutrient (nitrogen or sulfur) supplemented with 17 mM NaNO 2 , 85 mM NaNO 3 , 10 mM Na 2 SO 4 , and 10 mM NaHSO 3 . The nitrogen fixation capacity during 72 h was performed using the methodology described by Li et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological assessment of the strain was performed using BG-11 medium free of an essential nutrient (nitrogen or sulfur) supplemented with 17 mM NaNO 2 , 85 mM NaNO 3 , 10 mM Na 2 SO 4 , and 10 mM NaHSO 3 . The nitrogen fixation capacity during 72 h was performed using the methodology described by Li et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Thermophilic cyanobacteria are photoautotrophic prokaryotes that inhabit inhospitable niches, such as hot springs and other thermal environments. These thermophiles are essentially primary producers of the geothermal ecosystems with substantial ecological importance ( Esteves-Ferreira et al, 2018 ; Li et al, 2021 ). Besides, thermophilic cyanobacteria and their secondary metabolites have shown some potentials for biotechnological applications, including biosynthesis of thermostable metabolites and carbon valorisation vehicles ( Patel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the total nitrogen content of the former was higher than that of the latter, which might result from more core bacteria associated with N 2 fixation in the CSL treatment. This was also intrinsic to the higher total nitrogen content in the CSL treatment [ 46 48 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thermoleptolyngbya sp. B121 (Li et al., 2021), was isolated from the hot spring in Ganzi prefecture. Leptothermofonsia (Tang et al., 2022), a novel genus within the family Leptolyngbyaceae, was isolated from Lotus Lake hot springs situated in Ganzi prefecture.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the beneficial effects of free‐living soil cyanobacteria in such arid regions, including increased soil stability and improved soil fertility (e.g., Belnap & Gardner, 1993; Evans & Johansen, 1999; Muhlsteinova et al., 2014). Thermophilic cyanobacteria inhabit inhospitable niches, such as hot springs, and these thermophilic cyanobacteria are basically the main primary producers of the geothermal ecosystem and have important ecological significance (Esteves‐Ferreira et al., 2018; Li et al., 2021; Tang et al., 2022). However, despite the ecological importance of cyanobacteria in these habitats, we are still far from fully understanding the diversity of cyanobacteria in arid or semi‐arid soils and in hot springs.…”
Section: Introductionmentioning
confidence: 99%